Professional presenteeism in a context of scarcity of formal employment : the role of women employees in industrial enterprises of Mali - (:unkn) unknown (My University, 2018)
We began this PhD research on the topic of absenteeism in industrial plants of Mali. This study on absenteeism allowed me to mention the regular presence of some women at work. That is why; the PhD Director Pascale de Rozario recommended focusing our research on this topic. The implementation and processing of data in liaise with the theoretical model of Max Weber allowed to identify four ideal types of presenteeist employee women: The traditional presenteeist woman influenced by funerals and burials. The affective presenteeist woman influenced by colleagues and managers’ support. The valued presenteeist woman whose behavior is justified by relatives support and her financial contribution towards those relatives. The rationale presenteeist influenced by standing orders and financial punishments resorting to respect of statutory acts.
Keywords: African Research